Choosing the Right Data Deployment Architecture in Industry 4.0: From Sensors to Decisions - Rohith Kumar Punithavel; Thiagarajan Chidambareswaran (Utilitas Mathematica, 2025)
The future of manufacturing is not about producing more; it is about producing smarter and more efficiently. Industry 4.0 combines advanced technologies such as the Internet of Things (IoT), artificial intelligence (AI), and big data into manufacturing and supply chain practices. Modern machines come with smart sensors and connected systems that enable the acquisition of data that can be used to inform a wide variety of data-driven decisions, such as predictive maintenance, quality assurance, optimizing energy use, and production governing. However, the value of this data is not apparent until it has been properly processed and analyzed. Analytics, machine learning, and real-time processing frameworks transform the data into information and provide actionable decision-making ability so that firms can be forewarned of future failure, optimize resource consumption, and respond proactively to dynamic challenges of an industrial environment. This paper presents a comparative study of four primary approaches to data deployment architecture in Industry 4.0: on-prem, near-prem (edge), cloud, and hybrid, highlighting their strengths and weaknesses. Latency requirements, security, cost, scalability, and regulatory compliance are often determining constraints to help the industry choose one of these approaches. The study contributes by offering a structured evaluation of data deployment architectures and providing practical guidelines to align architectural choices with industrial needs, thereby supporting more effective adoption of Industry 4.0 strategies.